Socioeconomic dissociations in the neural and cognitive bases of reading disorders. (December 2022) - Romeo, Rachel R.; Perrachione, Tyler K.; Olson, Halie A.; Halverson, Kelly K.; Gabrieli, John D.E.; Christodoulou, Joanna A.
Abstract: Childhood socioeconomic status (SES) strongly predicts disparities in reading development, yet it is unknown whether early environments also moderate the cognitive and neurobiological bases of reading disorders (RD) such as dyslexia, the most prevalent learning disability. SES-diverse 6–9-year-old children (n = 155, half with RD) completed behavioral and functional magnetic resonance imaging (fMRI) tasks engaging phonological and orthographic processing, which revealed corresponding double-dissociations in neurocognitive deficits. At the higher end of the SES spectrum, RD was most strongly explained by differences in phonological skill and corresponding activation in left inferior frontal and temporoparietal regions during phonological processing—widely considered the "core deficit" of RD. However, at the lower end of the SES spectrum, RD was most strongly explained by differences in rapid naming skills and corresponding activation in left temporoparietal and fusiform regions during orthographic processing. Findings indicate that children's early environments systematically moderate the neurocognitive systems underlying RD, which has implications for assessment and treatment approaches to reduce SES disparities in RD outcomes. Further, results suggest that reliance on high-SES convenience samples may mask critical heterogeneity in the foundations of both typical and disordered reading development. Highlights: Socioeconomic status (SES) moderates which deficits explain reading disorders (RDs). RD in higher-SES children is best explained by reduced phonological skills. These children exhibit reduced activation in phonological processing brain regions. Instead, RD in lower-SES children is best explained by reduced rapid naming skills. These children exhibit reduced activation in orthographic processing brain regions.